PENGARUH PENETAPAN HARGA ACUAN MINYAK KELAPA SAWIT, FDI, NILAI TUKAR RUPIAH TERHADAP NERACA TRANSAKSI INDONESIA - Cahyanata, Komang Mas Aditha; Utama, Made Suyana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 6 (2022): VOL 11 NO 6, JUNI 2022 [2045-2480], 2022)
The value of trade balance is an important aspect that should be considered in any policy formulation by the government and will determine the direction of the country's economic policy, especially in terms of macro-scale policies. This study aims to determine the effect of the reference price of palm oil, FDI and the rupiah exchange rate simultaneously and also partially on Indonesia's current account balance in 2015, 1st Quarter to 2019 4th Quarter. The data used in this study are secondary data. The analysis technique used in this research is multiple linear regression analysis with the validity test. The test results show that 1) the reference price for palm oil, FDI and the rupiah exchange rate simultaneously have a significant effect on Indonesia's current account balance for 2015, quarter 1 - 2019, quarter 4; 2) the reference price for palm oil and FDI has a positive but insignificant effect on Indonesia's current account balance for 2015, quarter 1 - 2019, quarter 4; 3) The rupiah exchange rate has a significant negative effect on the current account balance in 2015, quarter 1 - 2019, quarter 4. Keywords: Determination of Palm Oil, Foreign Investment, Rupiah Exchange Rate, Current Account Balance.